EFEKTIVITAS PENGGUNAAN TEKNOLOGI AUGMENTED REALITY (AR) DAN VIRTUAL REALITY (VR) DALAM PEMBELAJARAN ANATOMI: TINJAUAN LITERATUR - Nadia Purnama Dewi,; Ade Teti Vani,; Dessy Abdullah,; Irwan Triansyah, (Nusantara Hasana Journal, 2025)
Technologies such as Augmented Reality (AR) and Virtual Reality (VR) have created new ways to learn anatomy, especially in medical instruction. This literature review aims to determine the effectiveness of virtual reality (VR) and augmented reality (AR) in improving student comprehension, retention, and engagement in anatomy learning. Studies published from 2017 to 2024 looked at trends, these studies were published from 2017 to 2024 and looked at trends, weaknesses, and shortcomings of these technologies. The review results indicate that AR and VR are capable of significantly enhancing the learning experience compared to conventional methods, especially through three- dimensional visualisation, interactivity, and realistic simulations. However, issues such as teacher readiness, hardware limitations, and implementation costs hinder widespread adoption. The review concludes that while AR and VR have not completely replaced traditional methods, they have great potential as effective complements in modern anatomy learning. Recommendations are provided for further research and more systematic integration strategies into medical education curricula.